Addition Of Cryptographic Algorithm For Bitmap Image Security Of Medical Record Information System Electronics (Rme) - Sri Wulandari; Muhammad Allam Arkani; Lucky Nurcahya Wibowo; Karunia Cinta Andini; Christina Ika Permatasari; Safitri Ima Yunita (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
In the daily use of technology, humans cannot be separated from the internet as a need to exchange information. People at this time spend more time in front of computer screens, laptops, even smartphones to find out information, send data to some of their friends. One of the information that is often sought or sent is a file. Apart from that, image files are files that are much searched for and sent, and many also contain important information in them. Image file security is of course very important so that unauthorized parties do not hack or manipulate information from the image. There is a way to secure information so that it does not leak to unauthorized parties, namely by using cryptography and steganography. By combining these two methods, you can maintain the confidentiality and security of a file, especially image files. In this study the algorithm and method used is the AES cryptographic algorithm (Advanced Encryption Standard) 256 and the LSB (Least Significant Bit) steganography method. Data integrity needs to be tested to ensure that the encryption and decryption processes are running properly. Data integrity testing uses the SHA-1 method. Likewise, the image quality after insertion will experience a decrease in quality. To evaluate this, it is necessary to test using the PSNR method. From the results of data integrity testing by comparing the hash value of the decrypted image file with the original image file, there is no difference. So this shows that the encryption and decryption process was successful. While in testing using the PSNR method, the average PSNR value is 44.14086 dB and with an average error value of 2.830403 dB, which means there is a small decrease in quality. From the implementation and testing results, it can be concluded that the AES 256 cryptographic algorithm and the steganography method LSB can be implemented in maintaining the confidentiality and security of secret messages.